Back Bending Phenomena Evaluation and Energy Band Crossing of Some Deformed Nuclei - العلوي، ايمان طارق; عبيد، علي خلف; إبراهيم، خالد سلمان (الجامعة المستنصرية - كلية التربية, 2016)
تم في هذا البحث استخدام ثلاثة نماذج من نماذج عزم القصور الذاتي هي VMI,VAVM,(GVMI) لغرض دراسة التركيب النووي لبعض الانوية الزوجية-الزوجية التي تنتمي إلى التناظرات O(6),SU(5)-O(6)-SU(3),SU(5),O(6)-SU(5),SU(3)-SU(3),SU(3)-O(6) على التوالي من خلال دراسة ظاهرة تقاطع حزم الطاقة (مستويات الطاقة كدالة للزخم الزاوي) وظاهرة الانحناء الخلفي (عزم القصور الذاتي(29/h2) ومربع الطاقة الدورانية (ho)2 أظهرت الدراسة الحالية للنماذج الثلاثة المستخدمة انه لا تأثير لعزم القصور الذاتي على شكل الانوية الدورانية عند التناظر الديناميكي SU(3) لعدم ظهور الانحناء الخلفي في الحزم التي تنتمي إلى هذا التناظر. أما بالنسبة للنتاظرات الديناميكية الأخرى فقد تبين وجود تأثير لعزم القصور الذاتي على تركيبها النووي بسبب ظهور ظاهرة الانحناء الخلفي.
In the present work, the moment of inertia models(VMI,VAVM,GVMI)are used to study the nuclear structure of even-even nuclei ( 56 26 Fe30, 74 34 Se40, 88 40 Zr 48, 106 46 Pd60, 156 46Gd92, 180 72 Hf108, 186 74 W112). These nuclei are belong to a dynamical symmetry O(6), SU(5)-O(6)-SU(3), SU(5), O(6)-SU(5), SU(3)-SU(5), SU(3), SU(3)-O(6) respectively, throw the study energy band crossing (energy level as a function of angular momentum), and back bending phenomena (moment of inertia (2/ħ2) as a function of rotational energy squared (ћω)2).This study shows that the three moment of inertia models that are used here have no effect on the nuclear structure of the nucleus with the dynamical symmetry SU(3), but the nuclear structure of the other dynamical symmetries have been effected, because the back bending does appear in them .
Keywords: الانوية المشوهة -- الفيزياء النووية